TAXONOMIC RELATIONS IN SURAH AR-RAHMAN - Muhammad Iqbal; Novria Grahmayanuri (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2019)
Quran is the guidance from Allah for all the muslims which is contained of prohition and command derived by Arabic Language. All Muslims have not been surely understand with Arabic Language. Thus, there are so many translation of Quran. The most important is the meaning included in Quran should be understood by Muslims. This study analyzes the meaning of Surah Ar-Rahman based on the relations of each elements of word realized in Taxonomic Relations from Martin and Rose (2007). It is analyzed by qualitative data analysis. The data is taken from the Quran Tafsir App by Ibnu Katsir from the verse 1-78. The data of the study are clauses contained taxonomic relations by applied interactive models of Miles, Huberman, and Saldana (2014). The findings of the analysis found four types of taxonomic relations in Surah Ar-Rahman, included repetition, contrast, class, and member. Repetition is the most frequently type found. It is indicated that this Suroh aims to warn men and jinn for grateful in every favors of Allah.